Swing and launch parameters in approach-iron shots hit with varying height and trajectory in golf - Robertson, S.; Burnett, A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The first aim of this study was to determine whether relationships existed between variability of swing and launch parameters and variability in shot outcome for straight golf shots. The second aim was to determine whether differences existed for swing and launch parameters in shots intentionally played with varying height and trajectory. Elite (n=20) and high-level amateur (n=22) golfers hit; 1) five straight shots of normal height and 2) nine shots of differing height (low, normal, high) and trajectory (straight, draw, fade). Variability of club attack angle, face angle and ball spin axis was significantly associated (p<0.05) with variability in shot outcome. Further, several significant differences (p<0.007) for swing and launch parameters were found between shot type. Results from this study may assist coaches in providing real time feedback to their golfers.